PENINGKATAN KEMAMPUAN NUMERASI MELALUI PENGGUNAAN MEDIA PAPAN BERHITUNG (PATUNG) PADA SISWA KELAS 1 SEKOLAH DASAR - Amalia Chayaningtyas; Hendra Erik Rudyanto; Dera Suci Aprilia Sari (CV. ADIBA ASIHA AMIRA, 2024)
This study aims to improve numeracy skills through the use of counting board media (statues) in grade 1 students of SDN Banjarsari wetan 01 trading Madiun district. This study used classroom action research involving seven students as participants. The methods used by researchers are; data collection methods using tests. The results showed that the use of counting board media can significantly improve the numeracy ability of addition 1-20 in grade 1 students. The use of counting board media in mathematics learning with addition material 1-20 was stated to increase after using counting board media from pre cycle 1 with an average value of 50, cycle 1 experienced an increase in the average value of 65, cycle 2 experienced an increase in the average value of 80. This indicates that the use of counting board media is very effective in improving numeracy skills in grade 1 students.